Understanding and implementing different modes of pacemaker - Kurcheti, Krishna Kiran (Kansas State University, 2012)
The Heart is a specialized muscle that contracts regularly and continuously, pumping blood to the body and the lungs. Heart’s natural Pacemaker, the SA node is responsible for this pumping action by causing a flow of electricity through the heart. These electrical impulses cause the atria and ventricles to contract and thereby pump the blood to different parts of the body. Malfunction of the SA node leads to a disturbance in the heart’s rhythm in which heart beats lower than 60 times a minute ending up with Bradycardia. It also leads to ventricular arrhythmia which disrupts the ability of the ventricles to pump blood effectively to the body. This can cause a loss of all blood pressure leading to cardiac arrest and eventually death. In order to restore the heart’s natural healthy rhythm, an artificial pacemaker is necessary. A Pacemaker adapts to the present condition of the heart and responds to the heart by either pacing or just sensing it. It paces whenever there is some problem in the heart’s electrical activity and inhibits the pace when there is a proper intrinsic beat. There are various modes in which Pacemaker can operate based on the condition of the heart. Ventricles and atria are individually paced in few modes such as VOO, VVT, VVI, AOO, AAT, and AAI and paced together in some modes such as DVI, DI, DDD, DDDR as per the requirement of the heart. The main goal of this report is to understand the various modes, their nomenclature, working strategy, developing the pseudo code and implementing different modes namely VOO, AOO, VVI, AAI, VVT and AAT modes using an academic, dual chamber pacemaker.
Keywords: Pacemaker modes; Electrical system of heart; Heart beat; Atria ventricles; Timing cycles of pacemaker; Pacing and sensing; Biomedical Engineering (0541); Computer Engineering (0464); Computer Science (0984)